Assessing the clinical severity of the Omicron variant in the Western Cape Province, South Africa, using the diagnostic PCR proxy marker of RdRp target delay to distinguish between Omicron and Delta infections – a survival analysis. (May 2022) - Hussey, Hannah; Davies, Mary-Ann; Heekes, Alexa; Williamson, Carolyn; Valley-Omar, Ziyaad; Hardie, Diana; Korsman, Stephen; Doolabh, Deelan; Preiser, Wolfgang; Maponga, Tongai; Iranzadeh, Arash; Wasserman, Sean; et al.
Highlights: Lower risk of admission with Omicron compared with contemporaneous Delta cases Analysis adjusted for vaccination status and prior diagnosed infection Compares contemporaneous cases, which is more robust than other South African studies Only the second study from a low middle income country assessing Omicron with contemporaneous cases Shows ongoing utility of novel proxy marker (RdRp target delay on Seegene Allplex assay) Abstract: Background: At present, it is unclear whether the extent of reduced risk of severe disease seen with SARS-Cov-2 Omicron variant infection is caused by a decrease in variant virulence or by higher levels of population immunity. Methods: RdRp target delay (RTD) in the Seegene Allplex TM 2019-nCoV PCR assay is a proxy marker for the Delta variant. The absence of this proxy marker in the transition period was used to identify suspected Omicron infections. Cox regression was performed for the outcome of hospital admission in those who tested positive for SARS-CoV-2 on the Seegene Allplex TM assay from November 1 to December 14, 2021 in the Western Cape Province, South Africa, in the public sector. Adjustments were made for vaccination status and prior diagnosis of infection. Results: A total of 150 cases with RTD and 1486 cases without RTD were included. Cases without RTD had a lower hazard of admission (adjusted hazard ratio [aHR], 0.56; 95% confidence interval [CI], 0.34-0.91). Complete vaccination was protective against admission, with an aHR of 0.45 (95% CI, 0.26-0.77). Conclusion: Omicron has resulted in a lower risk of hospital admission compared with contemporaneous Delta infection, when using the proxy marker of RTD. Under-ascertainment of reinfections with an immune escape variant remains a challenge to accurately assessing variant virulence.